Analysis of Adaptive Governance Dynamics in Socio-Ecological System-Based Disaster Risk Management - Arvind Kumar Subramaniam (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study aims to analyze the dynamics of adaptive governance in socio-ecological system-based disaster risk management and to examine how collaboration, learning, and adaptation influence disaster resilience in vulnerable areas. The study also identifies key factors that support and constrain the effectiveness of adaptive governance in reducing disaster risks. Subjects and Methods: This study employed a qualitative approach using a case study design. Research subjects consisted of 15 key informants, including local government officials, village representatives, community members, community groups, and non-governmental organizations selected through purposive and snowball sampling. Data were collected through in-depth interviews, focus group discussions, participant observation, and secondary document analysis. Data analysis was conducted using thematic coding based on the socio-ecological systems framework, supported by triangulation and member checking to ensure validity. Results: The findings revealed four major themes. First, socio-ecological dynamics significantly influenced disaster vulnerability through ecological degradation, climate variability, and livelihood dependency. Second, adaptive governance operated through multi-actor collaboration, social learning, and policy flexibility, with collaboration emerging as the dominant mechanism. Third, disaster experience, community awareness, government support, and social networks strengthened adaptive capacity, while weak coordination, limited budgets, delayed information, and program discontinuity constrained governance effectiveness. Fourth, adaptive governance improved disaster risk management outcomes by increasing household evacuation knowledge from 46% to 78%, participation in preparedness activities from 38% to 74%, and reducing evacuation response time from 52 to 29 minutes. Conclusions: Adaptive governance significantly strengthens disaster resilience by improving collaboration, adaptive learning, and institutional responsiveness, although stronger coordination and sustained resource commitment remain essential for long-term resilience.